PAX1 and SEPT9 methylation analyses in cervical exfoliated cells are highly efficient for detecting cervical (pre)cancer in hrHPV-positive women - Lulu He; Xiping Luo; Qiaowen Bu; Jing Jin; Shuai Zhou; Shaoyi He; Liang Zhang; Yu Lin; Xiaoshan Hong (Taylor & Francis Group, 2023)
Studies have investigated PAX1 and SEPT methylation were closely associated with cervical cancer. For this study, we verified the expressions of PAX1 and SEPT9 methylation in 236 hrHPV women cervical exfoliated cells by using quantitative methylation-specific PCR and we further explored their diagnostic value in cervical (pre)cancer detection. Our results identified that the methylation rates and levels of PAX1 and SEPT9 increased with cervical lesion severity. For a diagnosis of cervical (pre)cancer, the area under the curve (AUC) of PAX1 methylation was 0.77 (95% CI 0.71-0.83) and the AUC of SEPT9 methylation was 0.86 (95% CI 0.81∼0.90). Analyses of the PAX1 and SEPT9 methylation statuses alone or combined with commonly used tests can efficiently identify cervical (pre)cancer. In particular, SEPT9 methylation might serve as an effective and powerful biomarker for the diagnosis of cervical (pre)cancer and as an alternative triage test in HPV-based cervical (pre)cancer screening programs.Impact Statement What is already known on this subject? This subject showed that PAX1 and SEPT9 methylation were closely associated with cervical cancer. The methylation rates and levels of PAX1 and SEPT9 increased with cervical lesion severity and reached a peak in cervical cancer exfoliated cells. We further assessed the diagnostic performances of PAX1 and SEPT9 methylation in cervical cancer screening. In detecting cervical (pre)cancer, the sensitivity values of PAX1 and SEPT9 methylation were up to 61.18% and 82.35%, respectively, and the specificity values of PAX1 and SEPT9 methylation were up to 95.36% and 86.75%, respectively. Moreover, the ROC curve analysis showed AUC values of 0.77 for PAX1 methylation and 0.86 for SEPT9 methylation tests, which were significantly superior to other commonly used tests. These findings suggest that PAX1 and SEPT9 methylation detection may have great clinical potential in cervical cancer screening. What the results of this study add? The rates and levels of PAX1 and SEPT9 methylation increased with the severity of the cervical lesions. For a diagnosis of cervical (pre)cancer, the area under the curve (AUC) of PAX1 methylation was 0.77 (95% CI 0.71-0.83), and the sensitivity and specificity values were 61.18% and 95.36%, respectively. The AUC value of the SEPT9 methylation was 0.86 (95% CI 0.81 ∼ 0.90), and the sensitivity and specificity values were 82.35% and 86.75%, respectively. Compared with the various tests we conducted, the PAX1 methylation showed the highest specificity (95.36%), and the SEPT9 methylation demonstrated the highest accuracy(86.00%). What the implications are of these findings for clinical practice and/or further research? The methylation levels of PAX1 and SEPT9 had a certain predictive effect on the severity of cervical lesions in hrHPV-positive women. In addition, SEPT9 methylation analysis performs better than PAX1 methylation analysis and commonly used tests in cervical exfoliated cells for detecting cervical (pre)cancer in hrHPV-positive women. SEPT9 methylation analysis merits consideration as an effective and objective, alternative triage test in HPV-based cervical (pre)cancer screening programs.